Effects of Habitat and Competition on Niche Partitioning and Community Structure in Neotropical Ants - Salas-López, Alex; Violle, Cyrille; Munoz, François; Menzel, Florian; Orivel, Jérôme (Frontiers in Ecology and Evolution, 2022)
Competition for limited resources can yield two contrasting outcomes in community structure, namely, either (i) dominance of most competitive species (with functional convergence of the traits conferring this ability), or (ii) niche partitioning of species occupying distinct resources. In addition, varying resource availability in different environmental contexts is expected to yield varying community dynamics and composition between the contexts (habitat filtering). We addressed resource-based ant community structure in a tropical ecosystem. We expected ant species to display varying trophic preferences and foraging behaviours, allowing habitat selection and niche differentiation in ant assemblages. We expected habitat filtering to occur between open and forested areas in the landscape mosaic, and competition to further influence local species co-occurrence. We assessed resource use in nine ant assemblages distributed in two habitats (i.e. forests and croplands). We devised two separate experiments using bait-traps to characterize ant species’ trophic preference (e.g. eating prey, seeds, sugars) and their ability to obtain a same resource in heterogeneous forms (e.g. on vegetation, litter, variable amounts…). The majority of baits offered were rapidly exploited in the two habitats suggesting important resource limitations. Forest and cropland ant communities differed however in the proportions of resources exploited, suggesting different competitive pressures towards specific resources between habitats. Within each habitat, ants preferentially exploited the same resources, suggesting habitat filtering, but locally, interspecific resource partitioning resulted in a reduction of resource overlap compared to habitat scale. Our study provides evidence of the effects of habitat filtering and competition for resource in tropical ant community structure. Our findings also suggest that niche filtering and partitioning are co-variant forces determining the identity of the species present in local assemblages.